Paloma Bianchi’s Choreographic Work Hacia as a Practice of Amerindian Perspectivism - Díez, Diana Delgado-Ureña (Revista Brasileira de Estudos da Presença, 2021)
This text analyzes Hacia (2019) as a critical choreographic device facing the problem of disenchantment of the world derived from the separation between nature and culture inherited from Modernity/coloniality. Hacia puts into practice two notions of Amerindian perspectivism: one that recognizes the relational agency of all entities in the world; and another which raises knowledge as a process of subjectivation that implies bodily, sensory and imaginative dimensions. This analysis proposes a dialogue between the areas of anthropology and contemporary performing arts creation in Brazil.